2007
DOI: 10.1080/13682820601171555
|View full text |Cite
|
Sign up to set email alerts
|

The grammatical morpheme deficit in moderate hearing impairment

Abstract: It is argued that, because of hearing factors, the children with HI are below a threshold for intake of spoken language input (a threshold easily reached by the controls). Thus, the children with HI are more input-dependent at the point in development studied and as such are more sensitive to input frequency effects. The findings suggest that optimizing or indeed increasing auditory input of GMs may have a positive impact on GM development for children with moderate HI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 22 publications
7
50
1
1
Order By: Relevance
“…As described at the beginning of this article, the current findings support the notion that grammar is particularly vulnerable to the effects of inconsistent auditory access, especially in the case of morphological markers that have short duration and reduced perceptual salience (e.g., third-person singular; "he walks"; Leonard, 1989). These results, in combination with others (Koehlinger et al, 2013;McGuckian & Henry, 2007), also highlight how early, consistent access to auditory information can serve as a protective mechanism for acquiring English morphological markers (as in the case of the full-time users). Note.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As described at the beginning of this article, the current findings support the notion that grammar is particularly vulnerable to the effects of inconsistent auditory access, especially in the case of morphological markers that have short duration and reduced perceptual salience (e.g., third-person singular; "he walks"; Leonard, 1989). These results, in combination with others (Koehlinger et al, 2013;McGuckian & Henry, 2007), also highlight how early, consistent access to auditory information can serve as a protective mechanism for acquiring English morphological markers (as in the case of the full-time users). Note.…”
Section: Discussionsupporting
confidence: 86%
“…For the nonusers, the apparent difficulty with using English morphological markers is consistent with findings by other researchers. For example, McGuckian and Henry (2007) showed that 7-year-old children with moderate HL demonstrated poor performance on measures of English morphology. Koehlinger et al (2013) examined language samples of 3-and 6-year-old children in the OCHL cohort and found that children with more auditory access (i.e., better audibility and younger ages at HA fitting) produced more obligatory verb morphemes compared with children with less auditory access.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, both morphemes are among those for which persistent errors are found. In a similar vein, McGuckian and Henry (2007) have shown that English-speaking 8-year-old children with HAs produce less third person singular and possessive -s morphemes (e.g., Jim's hat) than language-matched hearing peers.…”
Section: The Dutch Verbal Paradigm and Hypothesesmentioning
confidence: 80%
“…The literature on children with CIs and HAs frequently reports delays in the acquisition of syntax and morphology, indicating that this is a vulnerable language area for both groups (Brown 1984;Elfenbein and Hardin-Jones 1994;Norbury et al 2001;Young & Killen 2002;Wake et al 2004;Borg et al 2007;Hansson et al 2007;McGuckian & Henry 2007;Geers et al 2009;Hawker et al 2008;Moeller et al 2010;Caselli et al 2012;Koehlinger et al 2013). These studies show that school-age children with hearing loss produce more errors in the production of different types of morphemes, including determiners (e.g., a, the), pronouns (e.g., me, him), plural nouns (e.g., apples), and past tense (e.g., he walked).…”
Section: Morphological Development In Children With Hearing Lossmentioning
confidence: 99%
“…X, XXX-XXX Kiese-Himmel 2008), and pragmatics (Elfenbein et al 1994). For CHI, the domain of morphosyntax is the most vulnerable linguistic area (Elfenbein et al 1994;Norbury et al 2001;McGuckian & Henry 2007), with the possibility of morphosyntactic weaknesses persisting into adolescence and adulthood (Delage & Tuller 2007;Huysmans et al 2014;Tuller & Delage 2014). When acquiring grammatical skills, perceptual salience of the morphological markers (i.e., the relative amount of linguistic information present in the acoustic signal to be perceived) influences the order in which grammatical skills are established (Svirsky et al 2002).…”
Section: Linguistic Proficiency In Individuals With Chimentioning
confidence: 99%